2008
DOI: 10.1016/j.adhoc.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of network reconfiguration protocols for mostly-off sensor networks

Abstract: A new class of sensor network applications is mostly off. Exemplified by Intel's FabApp, in these applications the network alternates between being off for hours or weeks, then activating to collect data for a few minutes. While configuration of traditional sensornet applications is occasional and so need not be optimized, these applications may spend half their active time in reconfiguration every time when they wake up. Therefore, new approaches are required to efficiently "resume" a sensor network that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In their work, Li et al [11] identified with the mostly-off approach of Intel's Fab project. As a modification, they presented a low-power listening with flooding, as well as local update with suppression as a means of reducing latency and cost of flooding respectively, while enjoying the benefits of sleeping nodes.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…In their work, Li et al [11] identified with the mostly-off approach of Intel's Fab project. As a modification, they presented a low-power listening with flooding, as well as local update with suppression as a means of reducing latency and cost of flooding respectively, while enjoying the benefits of sleeping nodes.…”
Section: Related Workmentioning
confidence: 97%
“…As a modification, they presented a low-power listening with flooding, as well as local update with suppression as a means of reducing latency and cost of flooding respectively, while enjoying the benefits of sleeping nodes. Low power listening involves the periodic sampling of a channel by taking one or a few signal strength samples [11].…”
Section: Related Workmentioning
confidence: 99%
“…, (1) where n is the WSN designer defined cluster size and {p} refers to the nearest integer derived from the value p. The "-1" in the equation above is to account for the sink node which is not going to be part of any cluster. The other sequential PEARSH steps are as follows:…”
Section: Power Efficient Algorithm For Raising Sensor Half-life mentioning
confidence: 99%
“…In this paper we address the problem of energy ecient data gathering in mostly-o sensor networks applications [1]. It is assumed that the data from the sensor network is collected periodically at very low rates, i.e., greater than tens of minutes.…”
Section: Problem Statementmentioning
confidence: 99%
“…We apply a polling period optimization scheme similar to the one proposed in [1]. Polling during the synchronization phase of BailighPulse is optimized with respect to the protocol duty cycle:…”
Section: Moutmentioning
confidence: 99%